In vitro anticoccidial activity of essential oil microencapsulated against Eimeria spp (Agroindustrial Science, 2023)
The aim of this research was to evaluate the in vitro anticoccidial activity of microencapsulated essential oils from Lepechinia heteromorpha (Briq.) Epling and Salvia sagittata Ruiz & Pav., against non-attenuated sporulated oocysts of Eimeria spp of broiler chickens. The treatments were the concentrations of the microencapsulated in 2.5; 5; 10; 20; 30 and 50 mg/ml, 2.5% potassium dichromate negative control group and 4% formaldehyde positive control group. The destruction of oocysts in liquid medium was evaluated by microscopic counting and the results were verified after 24 and 48 h of incubation at 28 °C. Data were analyzed by analysis of variance, using SPSS version 25 software and Tukey's test. The results showed highly significant statistical differences between the microencapsulated, as well as in their concentrations, registering the greatest destruction of sporulated oocysts by the microencapsulated essential oil of Salvia sagittata Ruiz & Pav. at a concentration of 50 mg/ml at 48 h of incubation reaching 83.5% destruction of oocysts, this value being similar to 4% formaldehyde. Concluding that the microencapsulated essential oils studied destroy up to 83.5% of the sporulated oocysts of Eimeria spp.
Keywords: Anticoccidial activity; Eimeria spp; microencapsulated; essential oil; In vitro